Awareness and Readiness of Malaysian University Students for Emotion Recognition System - Ab Aziz, Nor Azlina; Abdul Aziz, Nor Hidayati; Binti Sayed Ismail , Sharifah Noor Masidayu; Khan, Chy Tawsif; Hasnul, Muhammad Anas; Rahman, Md. Armanur; Ab. Rahman, Tasiransurini; Ab. Aziz, Kamarulzaman (International Journal of Integrated Engineering, 2021)
Emotion Recognition System (ERS) identifies human emotion like happiness, sadness, anger, disgust and fear. These emotions can be detected via various modalities such as facial expression analysis, voice intonation, and physiological signals like the brainâ€™s electroencephalogram (EEG) and heartâ€™s electrocardiogram (ECG).  The emotion recognition system allows machines to recognized human emotions and reacts to it. It offers broad areas of application, from smart home automation to entertainment recommendation system to driving assistance and to automated security system. It is a promising and interesting field to be explored especially as we are moving towards industrial revolution 5.0. Therefore, a survey was conducted on the awareness and readiness of the usage of emotion recognition system among Malaysian youths, specifically among university students. The findings are presented here. Overall, positive orientation towards the technology is observed among the participants and they are ready for its adoption